Study of the plant COPII vesicle coat subunits by functional complementation of yeast Saccharomyces cerevisiae mutants. - Johan-Owen De Craene (Public Library of Science (PLoS), 2014)
The formation and budding of endoplasmic reticulum ER-derived vesicles depends on the COPII coat protein complex that was first identified in yeast Saccharomyces cerevisiae. The ER-associated Sec12 and the Sar1 GTPase initiate the COPII coat formation by recruiting the Sec23-Sec24 heterodimer following the subsequent recruitment of the Sec13-Sec31 heterotetramer. In yeast, there is usually one gene encoding each COPII protein and these proteins are essential for yeast viability, whereas the plant genome encodes multiple isoforms of all COPII subunits. Here, we used a systematic yeast complementation assay to assess the functionality of Arabidopsis thaliana COPII proteins. In this study, the different plant COPII subunits were expressed in their corresponding temperature-sensitive yeast mutant strain to complement their thermosensitivity and secretion phenotypes. Secretion was assessed using two different yeast cargos: the soluble α-factor pheromone and the membranous v-SNARE (vesicle-soluble NSF (N-ethylmaleimide-sensitive factor) attachment protein receptor) Snc1 involved in the fusion of the secretory vesicles with the plasma membrane. This complementation study allowed the identification of functional A. thaliana COPII proteins for the Sec12, Sar1, Sec24 and Sec13 subunits that could represent an active COPII complex in plant cells. Moreover, we found that AtSec12 and AtSec23 were co-immunoprecipitated with AtSar1 in total cell extract of 15 day-old seedlings of A. thaliana. This demonstrates that AtSar1, AtSec12 and AtSec23 can form a protein complex that might represent an active COPII complex in plant cells.